2020
DOI: 10.1186/s12879-020-05527-0
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient tuberculosis treatment leads to earlier and higher mortality in individuals co-infected with HIV in southern China: a cohort study

Abstract: Background Tuberculosis (TB) and Acquired Immune Deficiency Syndrome (AIDS) are leading causes of death globally. However, little is known about the long-term mortality risk and the timeline of death in those co-infected with human immunodeficiency virus (HIV) and Mycobacterium tuberculosis (MTB). This study sought to understand the long-term mortality risk, factors, and the timeline of death in those with HIV-Mycobacterium tuberculosis (MTB) coinfection, particularly in those with insufficient TB treatment. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
10
0
2
Order By: Relevance
“…[12] Despite the latest treatment outcome data showing a TB treatment success rate of 84% and antiretroviral therapy (ART) initiation rate of 88% for those with HIV-MTB co-infection in a 2015 cohort in China, [13] the mortality of those with HIV-MTB co-infection remains frustrating at 36.5% in southern China according to a recent 5-year-cohort study. [14] Various studies have reported an association between unsuccessful TB treatment and risk factors. However, inconsistent findings from previous studies have made it difficult to assess whether reported factors are applicable to the local environment.…”
Section: Yang Et Al • Medicine (2022) 101:48 Medicinementioning
confidence: 99%
“…[12] Despite the latest treatment outcome data showing a TB treatment success rate of 84% and antiretroviral therapy (ART) initiation rate of 88% for those with HIV-MTB co-infection in a 2015 cohort in China, [13] the mortality of those with HIV-MTB co-infection remains frustrating at 36.5% in southern China according to a recent 5-year-cohort study. [14] Various studies have reported an association between unsuccessful TB treatment and risk factors. However, inconsistent findings from previous studies have made it difficult to assess whether reported factors are applicable to the local environment.…”
Section: Yang Et Al • Medicine (2022) 101:48 Medicinementioning
confidence: 99%
“…Findings emphasize that sufficient TB treatment should be provided, the treatment success rates should be scaled up, and efforts toward early TB case-finding among people living with HIV are essential. 8 In the third case, the patient had uncontrolled diabetes and came to the polyclinic with a neck abscess. Pus analysis confirmed the presence of AFB.…”
Section: Discussionmentioning
confidence: 99%
“…This feature explains the latter's seeking medical help even in acute conditions, which excludes early diagnosis of an existing disease and reduces the likelihood of successful treatment. It also suggests a lack of understanding of possible risks and low motivation in treatment, which leads to a violation of the rules for taking medications in case of their free distribution and drug resistance because of such behavior (PDR-TB) [22][23][24].…”
Section: Discussionmentioning
confidence: 99%